2018
DOI: 10.1016/j.bja.2018.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravenous S-ketamine on the MAC of sevoflurane: a randomised, placebo-controlled, double-blinded clinical trial

Abstract: Background: Ketamine is routinely used in operating theatres, emergency departments, ICUs, and even outpatient units. Despite the widespread use of ketamine, only basic aspects of its interactions with inhalation anaesthetic agents are known, and formal testing of interactions in humans is lacking. The minimum alveolar concentration (MAC) of inhalation anaesthetics is used to guide the depth of anaesthesia, and several drugs are known to influence the MAC. The aim of this study was to investigate whether intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 29 publications
(25 reference statements)
0
15
1
1
Order By: Relevance
“…Studies report that ketamine provides a significant reduction in the minimum alveolar concentration (MAC) of sevoflurane. 26 Although, animal studies show a decrease in the MAC of sevoflurane with ketamine administration, 27,28 there was no difference in intraoperative opioid and sevoflurane consumption in our study.…”
Section: Discussioncontrasting
confidence: 47%
“…Studies report that ketamine provides a significant reduction in the minimum alveolar concentration (MAC) of sevoflurane. 26 Although, animal studies show a decrease in the MAC of sevoflurane with ketamine administration, 27,28 there was no difference in intraoperative opioid and sevoflurane consumption in our study.…”
Section: Discussioncontrasting
confidence: 47%
“…We recruited adult patients with an American Society of Anesthesiologists physical status of 1–2 scheduled for elective surgery under general anesthesia. To standardize the noxious stimulus, we only included patients undergoing breast surgery, as this usually requires a skin incision of 3–5 cm at the trunk ( 6 ). The patients' age was restricted to 30–65 years, as the MAC is relatively uniform in this age group ( 7 ).…”
Section: Methodsmentioning
confidence: 99%
“…Next, the surgeon was asked to perform a single incision of 3 to 5 cm and then pause for 1 min before continuation of the operation. The response to the skin incision was counted as positive if the patient exhibited “gross purposeful movement of the head or at least one extremity” within 1 min after the skin incision ( 6 ). The response to the skin incision was classified as negative if no such movement occurred within 1 min after the skin incision.…”
Section: Methodsmentioning
confidence: 99%
“…However, some research has suggested that the acute psychoactive effects, including the dissociative, psychotomimetic, and 'mystical' effects, experienced during or shortly after a sub-anesthetic dosage of ketamine administration, may be associated with its therapeutic benefits. Esketamine has twice the analgesic effect of racemic ketamine, has fewer side effects, such as hallucinations, results in a faster recovery, and is able to lower the sevoflurane MAC value (19). Esketamine also has sympathomimetic properties that cause less cardiorespiratory depression than other sedatives, which had been reported that propofol combined with esketamine exhibited a good safety profile and high reliability, was more conducive to the hemodynamics stability, alleviating surgical stress and inflammatory responses (20).…”
Section: Immunofluorescence Detection and Western Blotmentioning
confidence: 99%